Heterogeneous marine environments diversify microbial-driven polymetallic nodule formation in the South China Sea - Lai, Mingyan; Liu, Qian; Wang, Xiaogu; Sun, Dong; Ran, Lihua; Li, Xiaohu; Yang, Chenghao; Lu, Bo; Xu, Xue-Wei; Wang, Chun-Sheng (Frontiers in Marine Science, 2024)
Most studies on the genesis of polymetallic nodules suggested that nodules in the South China Sea (SCS) are hydrogenetic types; however, the complexity and the heterogeneity in hydrology and geochemistry of the SCS might cause different processes of nodule formation, impacting their application and economic values.Microbial-mediated ferromanganese deposition is an important process in nodule formation, but the related microbial potentials are still unclear in the SCS. In this study, we sampled inat three typical regions (A, B and C) of the SCS enriched with polymetallic nodules in the SCS. Firstly, we investigated environmental and microbial characteristics of through the water columns for determining the heterogeneity of upper seawater that directly influencedand its impact on deep-sea bottom environments. Then, microbial compositions and structuress in sediment cores, overlying waters and nodules (inside and outside) collected within the same site region (Dive141, Dive135 and Dive139 in regions A, B and C, respectively) were analyzed for inferring features of nodule environments. M, and microbial interactions betweenamong nodules and surrounding environments were estimated with collinear network analysis. The microbial evidences indicated that geochemical characteristics in deep-sea of the SCS that were key to the polymetallic nodule formation were severely affected by organic matter flux from upper water column. The sediment in at Dive141Region A was sub-oxic due to the large input of terrigenous and phytoplankton-derived organic matter, potentially enhancing the overflow of reduced metals from the porewater. The intense microbial interaction between nodules and surface sediment reinforced the origin of metals for the ferromanganese deposition from the sediment (diagenetic type). Contrarily, the sediments in other two regions B and Csites were relatively rich in oxygen, and metal ions could be majorly suppliedbe majorly from seawater (hydrogenetic type). The large discrepancy in microbial communities between nodule inside and remaining samples suggested that the nodules experienced a long-term formation process, consistent with the feature of hydrogenetic nodules. Overall, in the SCS, distributions and interactions of microbial communities in nodules and surrounding environments significantly contributed to the nodule formation in the SCS by manipulating biogeochemical processes that eventually determined the source and the fate of metal ions.